MiR-125b participates in the occurrence of preeclampsia by regulating the migration and invasion of extravillous trophoblastic cells through STAT3 signaling pathway. (4th March 2021) - Tang, Jiani; Wang, Dan; Lu, Jing; Zhou, Xiaoyu
Abstract: Preeclampsia (PE) is a major risk factor for maternal and fetal mortality. Studies showed that microRNAs (miRNAs) play important roles in PE, and are closely related to extra-villous trophoblastic proliferation and invasion. The current study determined miR-125b expression in PE patients, and explored the role of miR-125b in the occurrence and development of PE and its possible mechanism, aiming to provide a novel basis for the diagnosis and treatment of PE. The level of miR-125b in serum derived from pregnant women was measured by quantitative real-time polymerase chain reaction (qRT-PCR). Cell proliferation, invasion and migration of HTR-8/SVneo were determined by Cell Counting Kit-8 (CCK-8), Transwell and scratch assay, respectively. The target gene of miR-125b was predicted by Targetscan, and verified by luciferase reporter assay. The expressions of related proteins were determined by Western Blotting. The miR-125b level in the serum of PE patients was up-regulated as compared with normal pregnant women, and high level of miR-125b reduced cell proliferation, inhibited invasion and migration of HTR-8/SVneo as well as the expressions of STAT3, p-STAT3 and SOCS3, while low level of miR-125b produced the opposite results. STAT3 was predicted as the target gene of miR-125b, and the high level of miR-125b inhibited STAT3 signaling pathway. High expression of miR-125b may be involved in the occurrence of PE through inhibiting STAT3 pathway to inhibit the migration and invasion of extra-villous trophoblastic cells.